1967
DOI: 10.1007/bf01258477
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trauma on production of herpes interferon in guinea pigs

Abstract: The adverse effect of trauma on host resistance has been one of the basic concepts in immunology. Recent studies of virus-induced interferons have shown that their production was supressed by trauma-type conditions, such as those produced by X-ray irradiation (1), the administration of steroids (see 2) or antimetabolites (3--5) as well as cold (6--7) and stress (8).It is well known that, among viral infections, those of herpes simplex virus are particularly sensitive to traumatic insults to the hosts, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This concept originally emerged in animal studies designed to characterize individual cytokines. For example, circulating interferon (IFN) levels were markedly increased in mice following endotoxin administration or bacterial infection (663) or in guinea pigs subjected to burn injury (709). In discovering tumor necrosis factor-␣ (TNF-␣), Carswell et al (106) found that plasma TNF-␣ levels were increased by administering endotoxin to mice, a finding later extended to rats and rabbits (521).…”
Section: A Cytokine Elevation In Critical Illnessmentioning
confidence: 96%
“…This concept originally emerged in animal studies designed to characterize individual cytokines. For example, circulating interferon (IFN) levels were markedly increased in mice following endotoxin administration or bacterial infection (663) or in guinea pigs subjected to burn injury (709). In discovering tumor necrosis factor-␣ (TNF-␣), Carswell et al (106) found that plasma TNF-␣ levels were increased by administering endotoxin to mice, a finding later extended to rats and rabbits (521).…”
Section: A Cytokine Elevation In Critical Illnessmentioning
confidence: 96%
“…Biological and chemical agents. The method of preparation of purified herpes serum interferon has been described previously (17). The serum obtained 6 hours after the intravenous injection of 10 g p.f.u, of herpes simplex virus was used unmodified as the interferon-containing serum.…”
Section: Methodsmentioning
confidence: 99%
“…Administration of hydroeortisone every 24 hours after inoculation of the virus (Group A6) or in a single dose 24 hours after the inoculation (Group B 10) and its administration in a single dose 72 hours after the inoculation did not significantly change the survival time (Group AT). Herpes interferon given 24 and 48 hours after the inoculation in a dose of 1024 units (17) resulted in survival of only one of 15 guinea pigs (Group A9). Four of 8 guinea pigs survived when crude serum containing interferon (512 units) was given daily for 5 days and a smaller virus inoculum was used (Group ]312).…”
Section: Changes In Survival Timementioning
confidence: 99%
“…There have been many fewer studies on the pyrogenicity of other viruses. Pyrogenic activities have so far been reported with Western equine encephalitis virus (Fastier, 1952 ), coxsackievirus (King, 1962 , 1964 ) and herpesvirus (Tokumaru, 1967 , 1968 ). It was reported that no pyrogenicity was found with vaccinia virus (King, 1962 ) and also with poliovirus and echo virus (Siegert, 1967 ; Grossgebauer, 1967 ).…”
Section: Full Textmentioning
confidence: 99%